Role of Lactose free milk in Acute Diarrhea - عطية الجبوري, محمد; فرهود الجبوري, لؤي; راشد السعدون, عماد (Tikrit Journal of Pharmaceutical Sciences, 2023)
Acute diarrhea is a very common disease in developing countries and is the first cause of death in children under two years old. diarrhea associated lactose intolerance is a clinical syndrome of abdominal pain, diarrhea nausea, flatulence, bloating after ingestion of lactose containing foods that cause symptoms vary according to the amount of lactose consumed. 170 hospitalized patients admitted at Tikrit Teaching Hospital were divided into three groups 70 on lactose free milk, 50 on cow milk and 50 on breast milk to see the effects of lactose free formula on bowel motions, hydration state, stool consistency, and duration of hospitalization. The study showed that (77.14%) of those on LFF having four motions on 2nd day which indicating a significant decrease in bowel motions. Also the results revealed that (45.71%) of those on LFF were discharged after two days of hospitalization. The effects of LFF on state of hydration revealed that (67.14%) improved in the hydration status on the 2nd day of hospitalization. Results were concluded that LFF having a beneficial effect on acute diarrhea in children under two years.